2019
DOI: 10.7717/peerj.7849
|View full text |Cite
|
Sign up to set email alerts
|

HIF inhibitor topotecan has a neuroprotective effect in a murine retinal ischemia-reperfusion model

Abstract: Purpose The therapeutic approach for retinal ganglion cell (RGC) degeneration has not been fully established. Recently, it has been reported that hypoxia-inducible factor (HIF) may be involved with retinal neurodegeneration. In this study, we investigated neuroprotective effects of a HIF inhibitor against RGC degeneration induced in a murine model of retinal ischemia-reperfusion (I/R). Methods Eight-weeks-old male C57/BL6J mice were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 27 publications
3
18
0
1
Order By: Relevance
“…Based on our previous papers, retinal thinning and reduction in RGC number by retinal I/R was suppressed by administration of HIF inhibitors. 13,14 As expected, Hif-1α cKO mice showed significant suppression in retinal thinning (analyzed by total and inner retinal thickness) after I/R, in comparison with that in control mice (Figure 1D-F). When it comes to RGC death, Hif-1α cKO mice had significant suppression of I/R-induced RGC death, in comparison with that in control mice, analyzed by mean number of RGCs between Hif-1α cKO and control mice (Figure 1G,H).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Based on our previous papers, retinal thinning and reduction in RGC number by retinal I/R was suppressed by administration of HIF inhibitors. 13,14 As expected, Hif-1α cKO mice showed significant suppression in retinal thinning (analyzed by total and inner retinal thickness) after I/R, in comparison with that in control mice (Figure 1D-F). When it comes to RGC death, Hif-1α cKO mice had significant suppression of I/R-induced RGC death, in comparison with that in control mice, analyzed by mean number of RGCs between Hif-1α cKO and control mice (Figure 1G,H).…”
Section: Resultssupporting
confidence: 77%
“…Previously, changes in expressions of Hif-1α and the representative HIF target genes such as vascular endothelial growth factor a (Vegfa), glucose transporter 1 (Glut1) and 3-phosphoinositede-dependent protein kinase 1 (Pdk1) were seen in the whole retina by retinal I/R. 13,14 We could reproduce this finding, and upregulated expressions in those genes were suppressed in Hif-1α cKO mice (Figure 1A). Stabilization of HIF-1α was also examined after retinal I/R and there was no induction of HIF-1α in Hif-1α cKO mice (Figure 1B,C).…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…To identify dietary factors inhibiting HIF and examine the functions against ocular diseases, we have screened natural products and reported their therapeutic effects in animal models of retinal disorders (Kunimi et al, 2019a;Kunimi et al, 2019b;Miwa et al, 2019). We further screened natural products from another library and revealed that administration of Garcinia cambogia extract and its main ingredient hydroxycitric have HIF inhibitory effects, showing significant therapeutic effects in a murine laser-induced CNV model (Ibuki et al, 2019).…”
Section: Introductionmentioning
confidence: 99%